Corner impact and compression after impact (CAI) of thin-walled composite profile – An experimental study. (15th September 2020) - Gliszczynski, A.; Bogenfeld, R.; Degenhardt, R.; Kubiak, T.
Abstract: Experimental investigations of channel-section profiles subjected to compression after impacts (20 J and 30 J) leading to global failure are presented. The columns under discussion were made of an eight-layer GFRP laminate with quasi-isotropic, quasi-orthotropic and angle ply arrangements of layers. The profiles were impacted in the corner in three variants: perpendicularly to the flange, at an angle of 45 to the web and perpendicularly to the web. All impact cases were characterized by a high level of absorbed energy (over 75%), which led to a barely visible impact damage, extensive fiber rupture, visible cracks in the laminate or material continuity loss. The load carrying capacity of the profiles degraded by the corner impact always decreases in relation to the not-impacted structures but every case was characterized by stable, postbuckling equilibrium paths. The most dangerous scenario was the corner impact introduced perpendicular to the web.